PENGARUH MOTIVASI KERJA INTERNAL TERHADAP KEPUASAN KERJA PEGAWAI UNIVERSITAS KARIMUN - Fauzan Haqiqi, (Rekaman : Riset Ekonomi Bidang Akuntansi dan Manajemen, 2020)
This research was conducted at Karimun University, involving respondents who are employees at Karimun University, amounting to 38 people. The purpose of this study was to analyze the effect of internal work motivation on job satisfaction of Karimun University employees. The variables in this study include one independent variable, internal work motivation, and one dependent variable, employee job satisfaction. Analysis conducted on the results of research includes testing of research instruments, multiple linear regression analysis, classic assumption tests, and hypothesis testing. Partially, the variable Internal Motivation significantly on the Job Satisfaction of Karimun University Employees. In this study a significance level of 0.05 used with degrees of freedom (dk) = n-k-1, n = number of samples observed, k = number of independent variables, and 1 = number of dependent variables. By using degrees of freedom (dk) = 33, and a two-tailed test (1/2 = 2.5%), table obtained value of t table = 2.00. Because the value of t arithmetic = 4.099> t table = 2.00 so Ho is rejected which means accepting Hi. Based on the calculation results, it can be seen that Internal Motivation affects employee job satisfaction, so that statistically the effect is significant.